2014
DOI: 10.1189/jlb.3a0514-251r
|View full text |Cite
|
Sign up to set email alerts
|

Distinct role of FoxO1 in M-CSF- and GM-CSF-differentiated macrophages contributes LPS-mediated IL-10: implication in hyperglycemia

Abstract: Macrophages are a heterogeneous population of immune cells that are essential for the initiation and containment inflammation. There are 2 well-established populations of inflammatory macrophages: classically activated M1 and alternatively activated M2 macrophages. The FoxO family of transcription factors plays key roles in a number of cellular processes, including cell growth, metabolism, survival, and inflammation. In this study, we determined whether the expression of FoxO1 contributes polarization of macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 76 publications
3
78
0
3
Order By: Relevance
“…We found that BMs were partially polarized to M2 based on flow cytometry and PCR, suggesting that M-CSF polarized macrophages generate an increased number of anti-inflammatory factors. Granulocyte-macrophage (GM)-CSF induces macrophages to produce higher amounts of inflammatory factors (Chung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We found that BMs were partially polarized to M2 based on flow cytometry and PCR, suggesting that M-CSF polarized macrophages generate an increased number of anti-inflammatory factors. Granulocyte-macrophage (GM)-CSF induces macrophages to produce higher amounts of inflammatory factors (Chung et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these GM-CSF grown macrophages could produce even more extensive proinflammatory cytokines compared to M-CSF grown, INFγ/LPS polarized macrophages (preliminary data). Despite the remarkable inflammatory phenotype of GM-CSF grown macrophages, there is much confusion about the use of these cells because they have been used as both macrophages and DCs without any guiding criteria (Bhattacharya et al, 2011; Chung et al, 2015; Ganesh et al, 2009). Consequently, we sought to distinguish amongst the heterogenous populations of GM-CSF derived cells and especially focused on characteristics of GM-BMMs compared to GM-BMDCs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In monocytes for example, GM-CSF regulates the expression of TLR2 and has been shown to induce the expression of IL-12, TNF-α, and monocyte chemoattractant protein-1 (MCP-1) by JAK2/STAT5 signaling (82, 83). Similarly, in vitro treatment of macrophage lineage cells with GM-CSF shifts the polarization to an inflammatory M1 phenotype (Fig 1) that enables them to respond strongly to stimuli (84, 85). In contrast, when M-CSF is used as the sole stimulus, it shifts monocytes into an immunosuppressive M2 phenotype (86, 87).…”
Section: Introductionmentioning
confidence: 93%